Changes in and predictors of pain and mortality in patients with chronic obstructive pulmonary disease. (September 2020) - Bentsen, Signe B.; Holm, Are M.; Christensen, Vivi L.; Henriksen, Anne H.; Småstuen, Milada Cvancarova; Rustøen, Tone
Abstract: This longitudinal study of patients with chronic obstructive pulmonary disease (COPD) aimed to investigate changes in pain characteristics (i.e., occurrence, intensity, and interference) and covariates associated with pain from study enrollment to 12 months, and to investigate if the different pain characteristics were associated with 5-year mortality. In total, 267 patients with COPD completed questionnaires five times over 1 year. The mean age of the patients was 63 years (standard deviation: 9.0), 53% were women, and 46% had very severe COPD. Median number of comorbidities was 2.0 (range: 0–11) and 47% of patients reported back/neck pain. Mixed models and Cox regression models were used for analyses. In total, 60% of the patients reported pain at baseline, and 61% at 12 months. The mixed model analyses revealed that those with better forced expiratory volume in 1 s (% predicted), more comorbidities, only primary school education, and more respiratory symptoms reported significantly higher average pain intensity. Moreover, those with more comorbidities, more respiratory symptoms, and more depression reported higher pain interference with function. At the 5-year follow-up, 64 patients (24%) were deceased, and the cumulative 5-year mortality rate was 22% (95% confidence interval [19–25]). Older age, lower forced expiratory volume in 1 s (% predicted), and higher pain interference at enrollment were all independently and significantly associated with higher 5-year mortality. Our findings show that many patients with COPD have persistent pain, and awareness regarding comorbidities and how pain interferes with their lives is needed. Highlights: Pain is generally not among the listed symptoms in patients with COPD. No studies have examined changes of a broader spectrum of pain over time in COPD. No studies have examined the association between pain and mortality in COPD patents. Pain is a significant and long-lasting burden for COPD patients. We hope that our study may increase the awareness of pain in patients with COPD.